Seagrasses produce most of the soil blue carbon in three Maldivian islands - Macreadie, Peter I.; Wartman, Melissa; Roe, Philippa; Hodge, Jessica M.; Helber, Stephanie B.; Waryszak, Pawel; Raoult, Vincent (Frontiers in Marine Science, 2024)
Blue carbon is fast garnering international interest for its disproportionate contribution to global carbon stocks. However, our understanding of the size of these blue carbon stocks, as well as the provenance of carbon that is stored within them, is still poor. This is especially pertinent for many small-island nations that may have substantial blue carbon ecosystems that are poorly studied. Here, we present a preliminary assessment of blue carbon from three islands in the Maldives. The higher purpose of this research was to assess the feasibility of using blue carbon to help offset carbon emissions associated with Maldivian tourism, the largest Maldivian industry with one of the highest destination-based carbon footprints, globally. We used stable isotope mixing models to identify how habitats contributed to carbon found in sediments, and Loss on Ignition (LoI) to determine carbon content. We found that for the three surveyed islands, seagrasses (Thalassia hemprichii, Thalassodendron ciliatum, Halodule pinofilia, Syringodium isoetifolium, and Cymodocea rotundata) were the main contributors to sediment blue carbon (55 – 72%) while mangroves had the lowest contribution (9 – 44%). Surprisingly, screw pine (Pandanus spp.), a relative of palm trees found across many of these islands, contributed over a quarter of the carbon found in sediments. Organic carbon content (‘blue carbon’) was 6.8 ± 0.3 SE % and 393 ± 29 tonnes ha-1 for mangrove soils, and 2.5 ± 0.2% and 167 ± 20 tonnes ha-1 for seagrasses, which is slightly higher than global averages. While preliminary, our results highlight the importance of seagrasses as carbon sources in Maldivian blue carbon ecosystems, and the possible role that palms such as screw pines may have in supplementing this. Further research on Maldivian blue carbon ecosystems is needed to: 1) map current ecosystem extent and opportunities for additionality through conservation and restoration; 2) determine carbon sequestration rates; and 3) investigate options and feasibility for tourism-related blue carbon crediting. Overall, the opportunity for blue carbon in the Maldives is promising, but the state of knowledge is very limited.